WORKLOAD, WORK STRESS, AND WORK ENVIRONMENT ARE ESSENTIAL PREDICTORS OF TEACHER WELLBEING: EMPIRICAL STUDY - Muzakki Muzakki; Farida Fitrianing Arum (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2022)
This study aims to reveal the effect of workload, work stress, and work environment on teacher wellbeing. The research method used is a qualitative method that focuses on hypothesis testing. The sample used 57 teachers using multiple linear regression analysis techniques to test the construction of the built model. The results of this study reveal that workload, work stress, and work environment have a positive and significant effect on teacher wellbeing. The increase in the three constructs can also have implications for improving teacher wellbeing.